2012
DOI: 10.1186/1471-244x-12-149
|View full text |Cite
|
Sign up to set email alerts
|

Depression, suicidal ideation, and associated factors: a cross-sectional study in rural Haiti

Abstract: BackgroundSince the 2010 earthquake in Haiti, there has been increased international attention to mental health needs throughout the country. The present study represents one of the first epidemiologic studies of depression symptomatology, suicidal ideation, and associated factors in Haiti’s Central Plateau.MethodsWe conducted a cross-sectional, zone-stratified household survey of 408 adults in Haiti’s Central Plateau. Depression symptomatology was assessed with a culturally-adapted Kreyòl version of the Beck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 101 publications
3
39
0
1
Order By: Relevance
“…(22) This fact is confirmed in a study with the rural population in Lithuania that observed that women presenting older age and lower educational level presented a significant association with depression symptoms (7) (data not identified in the present study).…”
Section: Discussionsupporting
confidence: 75%
“…(22) This fact is confirmed in a study with the rural population in Lithuania that observed that women presenting older age and lower educational level presented a significant association with depression symptoms (7) (data not identified in the present study).…”
Section: Discussionsupporting
confidence: 75%
“…These individuals were identified by our concurrent epidemiological survey (Wagenaar et al, 2012) as having depressive symptomology. These case visits included referral to local mental health professionals if the counsellor deemed it necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The present project is part of mixed methods research examining perceptions, experiences, care seeking and supports available for persons with mental illness in Haiti’s Central Plateau (Hagaman et al, 2013; Kaiser, Kohrt, Keys, Khoury, & Brewster, 2013; Kaiser et al, 2014; Keys et al, 2012; Khoury et al, 2012; Wagenaar, Hagaman, Kaiser, McLean, & Kohrt, 2012; Wagenaar et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Outros estudos encontraram situação diferente, com predominância das tentativas de suicídio em moradores das áreas rurais. Esses autores conjeturam que os cuidados de saúde em zonas rurais é baixo e que a maioria das pessoas não possui acesso a cuidados de saúde primários, principalmente aos serviços de saúde mental, o que poderia atuar como fator de risco para a tendência suicida [14,24,25].…”
Section: Discussionunclassified